Safety and efficacy of drug eluting stents vs bare metal stents in patients with atrial fibrillation: A systematic review and meta-analysis - Sambola, Antonia (2020)
Objective: A systematic review and meta-analysis was performed to evaluate the safety and efficacy of drug-eluting stents (DES) vs bare-metal stents (BMS) in atrial fibrillation (AF) patients. Methods: We systematically searched 5 engines until May 2019 for cohort studies and randomized controlled trials (RCTs). Primary outcomes were major bleeding and major adverse cardiac events (MACE) including cardiac death, myocardial infarction, target vessel revascularization (TVR) or stent thrombosis. Effects of inverse variance random meta-analyses were described with relative risks (RR) and their 95% confidence intervals (CI). We also stratified analyses by type (triple [TAT] vs dual [DAT]) and duration (short-vs long-term) of antithrombotic therapy. Results: Ten studies (3 RCTs; 7 cohorts) including 10,353 patients (DES: 59.6%) were identified. DES did not show higher risk of major bleeding than BMS (5.6% vs 6.9%, RR 1.07; 95%CI, 0.89–1.28, p = 0.47; I2 = 0%) or MACE (12% vs 13.6%; RR 0.96; 95%CI 0.81–1.13, p = 0.60; I2 = 44%). Although, DES almost decreased TVR risk (6.4% vs 8.4%, RR 0.78; 95%CI, 0.61–1.01, p = 0.06; I2 = 15%). Stratified analyses by type and duration of antithrombotic therapy showed no differences in major bleeding or MACE between both types of stents. In DES, long-term TAT showed higher major bleeding risk than long-term DAT (7.7% vs 4.7%, RR 1.48, 95%CI 1.08–2.03, p = 0.01; I2 = 12%). For both types of stents, MACE risk was similar between TAT and DAT. Conclusions: In patients with AF undergoing PCI, DES had similar rate of major bleeding and MACE than BMS. DAT seems to be a safer antithrombotic therapy compared with TAT.